2023
DOI: 10.3389/fmed.2023.1199931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of internal jugular vein catheterization on intracranial pressure and postoperative cognitive function in patients undergoing robot-assisted laparoscopic surgery

Abstract: BackgroundWe aimed to evaluate the effects of internal jugular vein (IJV) catheterization on intracranial pressure (ICP) and postoperative delirium (POD) during robot-assisted laparoscopic surgery by measuring the optic nerve sheath diameter (ONSD).MethodsData from a prospective single-center cohort study, conducted from October 2021 to February 2022, were used. Forty out of 80 patients scheduled for laparoscopic radical hysterectomy or prostatectomy were assigned to the group receiving IJV catheterization (Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…31 Furthermore, a prospective single-centre cohort study showed that internal jugular vein catheterisation in robot-assisted surgeries elevated intracerebral pressure. 32 Apart from the abovementioned, increased CO 2 crossing the blood-brain barrier can induce consecutive intra-operative hypercarbia and acidosis, leading to cerebral hypoxaemia, 33,34 which is associated with the release of vascular factors and actuate-venous short circuit opening, eventually resulting in cognitive impairment such as increased sleepiness, confusion, and loss of memory ( [35][36][37][38]. Although these studies provide some insight on the effects of CO 2 on brain functions, much work is still needed to clarify the cellular mechanism underlying the correlation between CO 2 absorption and cognition in the RALRP in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…31 Furthermore, a prospective single-centre cohort study showed that internal jugular vein catheterisation in robot-assisted surgeries elevated intracerebral pressure. 32 Apart from the abovementioned, increased CO 2 crossing the blood-brain barrier can induce consecutive intra-operative hypercarbia and acidosis, leading to cerebral hypoxaemia, 33,34 which is associated with the release of vascular factors and actuate-venous short circuit opening, eventually resulting in cognitive impairment such as increased sleepiness, confusion, and loss of memory ( [35][36][37][38]. Although these studies provide some insight on the effects of CO 2 on brain functions, much work is still needed to clarify the cellular mechanism underlying the correlation between CO 2 absorption and cognition in the RALRP in our future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of pneumoperitoneum and the administration of anesthetic drugs during laparoscopic surgery can have an impact on the hemodynamic stability of patients and the smooth recovery of postoperative cognitive function ( 16 ). The use of anesthetic drugs can lead to a higher stimulation response, thereby significantly affecting cognitive function ( 17 , 18 ). This trial tries to compare the doses of analgesics and muscle relaxants administered per unit of time under two different anesthesia methods, as well as evaluate the postoperative recovery quality system.…”
Section: Introductionmentioning
confidence: 99%